Spatiotemporal characteristics of China’s industrial high-quality development and driving mechanism by technological innovation - WANG Jianshi, YU Shangkun, HU Rui, WANG Chengxin (Ziyuan Kexue, 2023)
[Objective] The study used the data of 30 provinces (municipalities and autonomous regions) of China from 2004 to 2018 to reveal the spatial and temporal change characteristics and efficiency decomposition of China’s high-quality development of industry based on the super-slacks-based measure (SBM) model and Malmquist-Luenberger (ML) index model, considering non-expected output. The Tobit panel regression model was used to explore the driving mechanism of technological innovation on the development. [Methods] The study used the data of 30 provinces (municipalities and autonomous regions) of China from 2004 to 2018 to reveal the spatial and temporal change characteristics and efficiency decomposition of China’s high-quality development of industry based on the super-slacks-based measure (SBM) model and Malmquist-Luenberger (ML) index model, considering non-expected output. The Tobit panel regression model was used to explore the driving mechanism of technological innovation on the development. [Results] (1) Temporally, China’s high-quality development efficiency of industry showed an overall fluctuating upward trend, and it roughly showed a step-like geographical divergence pattern decreasing from the southeast coast to the northwest inland in space. (2) The ML index and decomposition results show that the improvement of the level of China’s high-quality development of industry mainly came from technological progress, and technical efficiency had less influence. (3) Technological innovation had a significant positive driving effect on the efficiency of high-quality development of industry. However, there were regional heterogeneity in the impact, and the improvement of technological innovation level in the eastern, central, and western regions had a positive driving effect on the improvement of high-quality development level, while the relationship between technological innovation level and high-quality development of industry in the northeastern region was not significant. [Conclusion] Technological innovation was an important means to realize China’s high-quality development of industry, and it was recommended to promote the transformation of industrial development to green, low-carbon, and high-quality development by improving the mechanism of technological innovation, strengthening the cultivation of innovative talents, and narrowing the regional gap of technological innovation.